Archaeozoology of the Near East, VIII : Actes des huitièmes Rencontres internationales d’archéozoologie de l’Asie du Sud-Ouest et des régions adjacentes, Lyon, 28 juin-1 er juillet 2006 = Proceedings of the eighth International Symposium on the Archaeozoology of Southwestern Asia and Adjacent Areas - Archaeozoology of Southwestern Asia and adjacent areas. International symposium (08. : 2006 : Lyon). (Lyon)
2 c. (648 s.)